2009
DOI: 10.4161/cbt.8.13.8691
|View full text |Cite
|
Sign up to set email alerts
|

A novel peroxisome proliferator-activated receptor delta antagonist, SR13904, has anti-proliferative activity in human cancer cells

Abstract: The peroxisome proliferator-activated receptor delta (PPARdelta) is a ligand-activated, nuclear receptor transcription factor that has a documented role in glucose and lipid homeostasis. Recent studies have implicated this nuclear receptor in numerous aspects of oncogenesis. We report herein the characterization of a novel small-molecule (SR13904) that inhibits PPARdelta agonist-induced transactivation and functions as a PPARdelta antagonist. SR13904 also antagonizes PPARgamma transactivation, albeit with much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 53 publications
0
30
1
Order By: Relevance
“…Results from these studies are in contrast to a recent report suggesting that antagonism of PPAR␤/␦ with 10 M SR13904 inhibited cell proliferation of A549 cells (Zaveri et al, 2009). However, data from the present study and recent work by others (Shearer et al, 2010) show that antagonism of PPAR␤/␦ in the same human lung cancer cell line has no effect on cell proliferation at concentrations that specifically antagonize PPAR␤/␦.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Results from these studies are in contrast to a recent report suggesting that antagonism of PPAR␤/␦ with 10 M SR13904 inhibited cell proliferation of A549 cells (Zaveri et al, 2009). However, data from the present study and recent work by others (Shearer et al, 2010) show that antagonism of PPAR␤/␦ in the same human lung cancer cell line has no effect on cell proliferation at concentrations that specifically antagonize PPAR␤/␦.…”
Section: Discussioncontrasting
confidence: 55%
“…However, data from the present study and recent work by others (Shearer et al, 2010) show that antagonism of PPAR␤/␦ in the same human lung cancer cell line has no effect on cell proliferation at concentrations that specifically antagonize PPAR␤/␦. It is important to note that the study by Zaveri et al (2009) had limitations that preclude definitive conclusions regarding the specificity of the response observed with SR13904 because they did not demonstrate an increase in A549 cell growth by ligand activation of PPAR␤/␦ that was prevented by cotreatment with SR13904. This is a concern because no effect on cell proliferation is found in response to ligand activation of PPAR␤/␦ in A549 cells as shown by the present study and another recent report .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same research group recently developed the acrylonitrile compound DG172 (6) which exhibited potent PPARβ/δ antagonism and oral bioavailability [21]. As carboxylic acids are canonical agonists of the PPAR receptors, it is notable that also SR13904 (7) [22], reported by Zaveri et al as well as the acid 3a (8) [23], reported by Kasuga et al, exhibited PPARβ/δ antagonism. In 2010, Shearer et al reported the potent PPARβ/δ antagonist GSK3787 (9) [24] which displayed good oral pharmacokinetic properties.…”
Section: Introductionmentioning
confidence: 99%